2016
DOI: 10.1038/srep38295
|View full text |Cite
|
Sign up to set email alerts
|

γ-H2AX/53BP1/pKAP-1 foci and their linear tracks induced by in vitro exposure to radon and its progeny in human peripheral blood lymphocytes

Abstract: The biodosimetric information is critical for evaluating the human health hazards caused by radon and its progeny. Here, we demonstrated that the formation of phosphorylated histone variant H2AX (γ-H2AX), p53-binding protein 1 (53BP1) and phosphorylated KRAB-associated protein 1 (pKAP-1) foci and their linear tracks in human peripheral blood lymphocytes (HPBLs) in vitro exposed to radon and its progeny were dependent on the cumulative absorbed dose of radon exposure but was unrelated to the concentration of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…To reveal the DNA damage-and repair-associated protein distribution within the damage-loaded chromatin tracks, we applied SMLM ( Figure 1B,C) and quantitative analyses of chromatin conformations including statistical physics, graph theory and cluster algorithms to study repair protein arrangements. As noted by wide-field microscopy ( Figure 1A), alpha-induced DNA damage tracks in leukocyte nuclei showed several, more-or-less linearly aligned super-foci or continuous tracks that consisted of highly concentrated γ-H2AX fluorescent tags that represented the most abundant damage marker ( Figures 1B and 2A), as expected from earlier analysis [8,35,46,51,52]. At an even higher resolution, the super-foci could be subdivided into further subunits with characteristic signal accumulations (Figures 1 and 2).…”
Section: Distribution Of Dna Damage-associated Proteins In Ra-223-irrsupporting
confidence: 81%
See 1 more Smart Citation
“…To reveal the DNA damage-and repair-associated protein distribution within the damage-loaded chromatin tracks, we applied SMLM ( Figure 1B,C) and quantitative analyses of chromatin conformations including statistical physics, graph theory and cluster algorithms to study repair protein arrangements. As noted by wide-field microscopy ( Figure 1A), alpha-induced DNA damage tracks in leukocyte nuclei showed several, more-or-less linearly aligned super-foci or continuous tracks that consisted of highly concentrated γ-H2AX fluorescent tags that represented the most abundant damage marker ( Figures 1B and 2A), as expected from earlier analysis [8,35,46,51,52]. At an even higher resolution, the super-foci could be subdivided into further subunits with characteristic signal accumulations (Figures 1 and 2).…”
Section: Distribution Of Dna Damage-associated Proteins In Ra-223-irrsupporting
confidence: 81%
“…Active, monomeric ATM phosphorylates, among other downstream targets, the histone 2 variant H2AX at its Serine 139 moiety, forming γ-H2AX [21]. The latter is in various cell types the most prominent and persisting chromatin mark along alpha particle and accelerated ion tracks [31,51,53,64,65].…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage induced by α-particles, on the other hand, involves the generation of closely stacking DSBs and DNA modifications along the ionisation tracks that can be visualised in exposed nuclei as long tracks of γ-H2AX-positive chromatin and repair associated proteins when the ionisation tracks in the nuclei lie parallel to the focal plane of the observer 30 32 . It has been shown that the quantification of these tracks can be informative for biological dose estimation 24 , 33 , 34 . So far, this method has been used to quantify DNA damage to cultured human blood cells after external α-irradiation 24 and after radon gas exposure 33 , but not after internal irradiation with the clinically used α-emitter Ra-223.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the quantification of these tracks can be informative for biological dose estimation 24 , 33 , 34 . So far, this method has been used to quantify DNA damage to cultured human blood cells after external α-irradiation 24 and after radon gas exposure 33 , but not after internal irradiation with the clinically used α-emitter Ra-223.…”
Section: Introductionmentioning
confidence: 99%
“…has been adopted to better reproduce the saturation, with b and c free parameters of the fit. Linear fits have been applied in many studies to X-rayinduced foci yields at low doses (9) . The saturation following photon irradiation was instead assessed in the same dose range of this study when ICC is performed for the scoring (2) , while higher saturation thresholds were observed when the overall fluorescence intensity from the whole nucleus is recorded by means of flow cytometry (3) .…”
Section: Experimental Data On γ-H2ax Foci Inductionmentioning
confidence: 99%